The Benefit of Nutrition in Coronary Heart Disease - Benalikhoudja, H.; Abdelbaki, M.; Boudiaf , Djoudi E. (Clinical Medicine And Health Research Journal, 2023)
Coronary heart disease (CHD) is a condition of the coronary arteries that supply the heart. It is a narrowing of one or more coronary arteries. It is caused by atherosclerosis which is due to the action of fatty deposits of cholesterol. When blood flow is slowed by a blocked artery, the myocardium is no longer properly oxygenated. Coronary heart disease represents a major socio-economic challenge. In addition to genetics, the main risk factors for coronary heart disease are lack of physical activity, smoking, alcohol abuse and poor diet. The mortality rate linked to CD in the world and in Algeria is 34%. Our study involved 40 patients taken at random. It was carried out by collecting biological, clinical and anthropometric data collected during consultations. Our objective was to show the benefit of diet in the prevention of modifiable risk factors (hypertension, diabetes, dyslipidemia, obesity, sedentary lifestyle, smoking and alcohol) and compare our results with those found in the literature.